2018
DOI: 10.1590/s0100-204x2018000500005
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects on weeds and dry matter yields of cover crops

Abstract: The objective of this work was to evaluate the dry matter yield of cover crops and their suppressive effects on weeds. The experiment was carried out during three years in a cerrado area of the state of Goiás, Brazil, and consisted of 16 treatments with fallow and cover crops cultivated in single cropping and intercropping. Fallow allowed high weed infestation. Cover crops affected the composition of weeds, which showed greater diversity in fallow, followed by the Pennisetum glaucum 'BRS 1501' and Cajanus caja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…High dry matter values of a cover species are related to the good formation of straw on the soil, which guarantees a reduction in the establishment of weeds, by means of factors such as the thermal amplitude, little light availability and formation of physical barrier (Monquero et al, 2009;Ferreira et al, 2018).…”
Section: /9mentioning
confidence: 99%
“…High dry matter values of a cover species are related to the good formation of straw on the soil, which guarantees a reduction in the establishment of weeds, by means of factors such as the thermal amplitude, little light availability and formation of physical barrier (Monquero et al, 2009;Ferreira et al, 2018).…”
Section: /9mentioning
confidence: 99%
“…Congo grass produced 5,620 kg ha -1 of dry matter as a sole crop and from 4,643 kg ha -1 to 4,947 kg ha -1 when intercropped with sorghum, which are considered high dry mass production levels (Ferreira et al, 2018;Hirata et al, 2018). Urochloa forage species tend to produce large amounts of dry matter in off-season crops in the Cerrado region (Carvalho et al, 2017).…”
Section: Dry Mass Production For Sorghum and Grassesmentioning
confidence: 99%
“…An important differential in the NTS was the inclusion of ruzigrass intercropped with maize and as subsequent crop to soybean, acting as a cover plant and improving K cycling in the system. According to Ferreira et al (2018), the use of Poaceae species as cover crops (including ruzigrass) after the soybean harvest increases biomass production, providing soil protection and straw for subsequent cotton cultivation under no-till in the Cerrado region. Oliveira et al (2019) reported that maize intercropped with Urochloa brizantha produces a high amount of plant residues, in addition to nutrient cycling, including K. The same authors reported that plant biomass of U. brizantha or ruzigrass accumulated K similarly to or more than maize.…”
Section: Partial Potassium Balance and Exchangeable Potassium Pool In The Soil Profilementioning
confidence: 99%